Pd(OAc)2/Ph3P-catalyzed dimerization of isoprene and synthesis of monoterpenic heterocycles - Kellner, Dominik; Weger, Maximilian; Gini, Andrea; Mancheño, Olga García (Beilstein Journal of Organic Chemistry, 2017)
The palladium-catalyzed dimerization of isoprene is a practical approach of synthesizing monoterpenes. Though several highly selective methods have been reported, most of them still required pressure or costly ligands for attaining the active system and desired selectivity. Herein, we present a simple and economical procedure towards the tail-to-tail dimer using readily available Pd(OAc)2 and inexpensive triphenylphosphine as ligand. Furthermore, simple screw cap vials are employed, allowing carrying out the reaction at low pressure. In addition, the potential of the dimer as a chemical platform for the preparation of heterocyclic terpenes by subsequent (hetero)-Diels–Alder or [4 + 1]-cycloadditions with nitrenes is also depicted.
Keywords: dimerization; heterocycles; isoprene; monoterpene; palladium catalysis